Uprzemysłowienie powiatu sieradzkiego na kilka lat przed wybuchem I wojny światowej - Klemantowicz, Dariusz (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2012)
The District of Sieradz, located on the eastern border of the western province of the Kalisz – Lodz industrial area, was in existence before the First World War. Its peripheral location had a negative impact on the dynamic development of industry. Despite this, the district developed one important industrial centre, in Zdunska Wola, where a textile industry – dominated by large and small companies – exists together with food industry, minerals, wood and metal engineering. There was much competition from the industrial centres of Lodz, Pabianice, Zgierz and Tomaszow, in the region of Lodz. The small amount of industrial development was mainly decided by the district’s agricultural character and a weak domestic market. The railway connection between Lodz and Kalisz, which facilitated trade in goods, came too late. The district was attractive as a reservoir of cheap labour, and a place where finished products could easily be exported. In the province of Kalisz around 1910 was on the third place in terms of industrialization, shortly after the district Kalisz, where it operated the largest industrial centre of the province – Kalisz and Łęczyca, which played a large center of textile industry in Ozorków.